Clinical Study on the Causes and Outcome of Facial Nerve Palsy at Liaquat University Hospital Hyderabad - Sana Shabbir, Arisha Sana Memon, Gulshad Wagan, Sadia Effendi, Fahmida Gul, Kanwal Abbas Bhatti, (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: A facial paralysis can be enormously distressing for a person. In order to restore and rehab face symmetry, it is essential to understand the source and type of nerve damage. Lower motor neuron facial paralysis was investigated in the current study to assess its various causes. Patients and Method: This prospective study was carried out on 48 facial nerve palsy (FNP) in the Department of Medicine, Liaquat University Hospital, Hyderabad from January 2021 to August 2022. Patients diagnosed with peripheral facial nerve paralysis of any age and both genders were enrolled. Patient’s details such as time of symptom onset, paralysis duration, rapidity of progression, and paralysis completeness were evaluated. Each individual was interviewed about family history, medical illness such as malignancy, tuberculosis, diabetes, autoimmune disorders, previous episodes, any prior surgery, trauma history, and related symptoms such as neurological, auditory, and vestibular. Lesion site and treatment response was administered by Topo diagnostic tests. Data analysis was carried out in SPSS version 26. Results: Out of 48 FNP patients, 34 (70.8%) were male and female 14 (29.2%) respectively. The overall mean age was 35.8±6.2 years with an age range 5 to 70 years. Patients were distributed into different age groups as follows: 6 (12.5%) in 5-20 years, 19 (39.6%) in 21-35 years, 16 (33.3%) in 36-50 years, and 7 (14.6%) in 51-70 years. The prevalence of left and right side affected patients were 20 (41.7%) and 28 (58.3%) respectively. The most prevalent causes of FNP were idiopathic and external trauma found in 12 (25%) cases followed by infections and tumour found in 8 (16.7%) cases. Severity of paralysis calculated based on H. Brackman grading were as follows: Grade IV, V, and VI paralysis were found in 22 (45.8%), 8 (16.7%), and 2 (4.2%) respectively. Physiotherapy and conservative treatment was given to 26 (54.2%) patients followed by facial nerve surgery in 14 (29.2%) patients. Conclusion: The present study found that External trauma and Bell's palsy are the leading causes of LMN facial nerve paralysis. The right side was more affected than the left side, and male patients predominated. Upon presentation, most lesions were suprageniculate and had House Brackmann severity scores of IV. After a one-year follow-up, most of our peripheral facial paralysis cases had recovered fully or partially. Keywords: Facial nerve palsy, Outcomes, Causes, House Brackmann severity.